Role of alpha1 and alpha2-adrenoceptors of the lateral hypothalamic area on urinary excretion caused by centrally administered angiotensin II - Saad, Wilson Abrão [UNESP]; Camargo, Luiz Antonio de Arruda [UNESP]; Renzi, Antonio [UNESP]; Menani, José Vanderlei [UNESP]; Saad, Willian Abrão [UNESP] (Elsevier B.V., 1995)
To determine whether central α1 and α2-adrenergic mechanisms are involved in urinary sodium and potassium excretion and urine volume induced by angiotensin II (ANGII), these renal parameters were measured in volume-expanded Holtzman rats with cannulas implanted into lateral ventricle (LV) and lateral hypothalamus (LH). The injection of ANGII into LV in rats with volume expansion reduced the sodium, potassium and urine excretion in comparison to the control injections of isotonic saline, whereas prazosin (α1 antagonist) potentiated these effects. Clonidine (α2 agonist) and yohimbine (α2 antagonist) injected into LH previous to injection of ANGII into LV also abolished the inhibitory effect of ANGII. These results suggest that the discharge of central alpha-adrenergic receptors has dual inhibitory and excitatory effect on antinatriuretic, antikaliuretic and antidiuretic effect induced by central ANGII in volume-expanded rats. © 1995.
Keywords: Potassium; Sodium; Urinary volume; Alpha 1 adrenergic receptor; Alpha 1 adrenergic receptor blocking agent; Alpha 2 adrenergic receptor; Alpha 2 adrenergic receptor blocking agent; Alpha 2 adrenergic receptor stimulating agent; Alpha adrenergic receptor stimulating agent; Angiotensin; Clonidine; Potassium; Prazosin; Sodium; Yohimbine; Animal experiment; Controlled study; Hypothalamus; Male; Nonhuman; Priority journal; Rat; Urinary excretion; Animal; Drug effect; Drug interaction; Metabolism; Micturition; Rat strain; Angiotensin II; Animal; Clonidine; Drug Interactions; Hypothalamus; Male; Prazosin; Rats; Rats, Inbred Strains; Support, Non-U.S. Gov't; Urination; Yohimbine